2020
DOI: 10.1103/physrevx.10.031019
|View full text |Cite
|
Sign up to set email alerts
|

Field Dependence of Magnetic Disorder in Nanoparticles

Abstract: The performance characteristics of magnetic nanoparticles toward application, e.g., in medicine and imaging or as sensors, are directly determined by their magnetization relaxation and total magnetic moment. In the commonly assumed picture, nanoparticles have a constant overall magnetic moment originating from the magnetization of the single-domain particle core surrounded by a surface region hosting spin disorder. In contrast, this work demonstrates the significant increase of the magnetic moment of ferrite n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 80 publications
(105 reference statements)
3
52
0
Order By: Relevance
“…In the work of Herlitschke et al 28 no magnetic core-shell structure was reported for spherical particles with diameter of 7.4 nm and σ of a lognormal size distribution of 0.057 and the reduction of the magnetization was entirely ascribed to random orientations of atomic moments homogeneously distributed in the particle. A recent study by Zákutná et al 91 on cobalt ferrite nanoparticles with mean diameter of 14.1 nm and lognormal size distribution of σ = 0.031 revealed a magnetically disordered surface region of 0.7 nm thickness. Since the particles used there were composed of cobalt ferrite the results are only partially comparable to pure ferrite nanoparticles.…”
Section: Positionmentioning
confidence: 94%
“…In the work of Herlitschke et al 28 no magnetic core-shell structure was reported for spherical particles with diameter of 7.4 nm and σ of a lognormal size distribution of 0.057 and the reduction of the magnetization was entirely ascribed to random orientations of atomic moments homogeneously distributed in the particle. A recent study by Zákutná et al 91 on cobalt ferrite nanoparticles with mean diameter of 14.1 nm and lognormal size distribution of σ = 0.031 revealed a magnetically disordered surface region of 0.7 nm thickness. Since the particles used there were composed of cobalt ferrite the results are only partially comparable to pure ferrite nanoparticles.…”
Section: Positionmentioning
confidence: 94%
“…Using magnetic SANS, a significant reduction of surface spin disorder was found upon cooling to low temperatures of 10 K. [ 116 ] More recently, a strong field‐dependence of surface spin disorder was revealed, expressed by a gradual polarization of initially disordered surface spins even beyond the structurally coherent grain size (Figure 5h). [ 117 ] The field dependence of the spatial distribution of surface spin disorder ultimately gives access to the spatially resolved disorder energy toward the particle surface. [ 117 ]…”
Section: Defect‐induced Spin Disorder In Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…[ 117 ] The field dependence of the spatial distribution of surface spin disorder ultimately gives access to the spatially resolved disorder energy toward the particle surface. [ 117 ]…”
Section: Defect‐induced Spin Disorder In Iron Oxide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations